Fitz-hugh-curtis syndrome secondary to postpartum endometritis: Case Report and literature review - Silvia Amodeo; Giuseppe Paci; Giuseppe Cutaia; Bruno Murmura; Fabio Cannizzaro; Renato Venezia (Wolters Kluwer Medknow Publications, 2021)
We report a case of Fitz-Hugh-Curtis syndrome (FHCS) 1 week after an urgent cesarean section. Although its onset in the postpartum period is poorly reported in the literature, we suggest that FHCS can complicate puerperal endometritis; therefore, it should be consider in differential diagnosis in puerpera with right upper quadrant pain. Again, it can be useful to perform a contrast computed tomography that allows early diagnosis and conservative treatment.